Coevolution of cooperation, response to adverse social ties and network structure - Sven Van Segbroeck; Francisco C. Santos; Jorge M. Pacheco; Tom Lenaerts (Games, 2010)
Human social networks reshape continuously, as individuals forge new contacts while abandoning existing ones. Simultaneously, individuals adapt their behavior, leading to an intricate interplay been network evolution and behavior evolution. Here, we review a framework, called Active Linking, which allows an analytical treatment of such a co-evolutionary dynamics. Using this framework we showed that an increase in the number of ways of responding to adverse interactions leads an overall increase of cooperation, which is here extended to all two-player social dilemmas. In addition, we discuss the role of the selection pressure in these results.
Keywords: 330; social dilemmas; cooperation; evolutionary game theory; dynamical networks; coevolution; selection pressure